2018
DOI: 10.1159/000486157
|View full text |Cite
|
Sign up to set email alerts
|

Elevations of Thrombotic Biomarkers in Hemoglobin H Disease

Abstract: Background: Thalassemia is a group of hereditary hemoglobinopathies caused by decreased or absent synthesis of α and/or β globin chains. Studies have shown that hypercoagulability and thrombosis are common clinical symptoms in β-thalassemia, especially β-thalassemia intermedia, but little is known about in α-thalassemia. This study aims to examine phosphatidylserine (PS) levels, platelet activation, and coagulation markers in splenectomized (S) and nonsplenectomy (NS) patients with hemoglobin (Hb) H disease. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…However, the PS-exposed RBC levels in patients with thalassemia were higher than in normal controls. 10 Previous studies showed significantly elevated levels of PS-exposed RBCs in β-thalassemia/Hb E patients who underwent splenectomy and were associated with pulmonary hypertension. 11 This study demonstrated a correlation between PS-exposed RBCs levels and EMH in patients with thalassemia.…”
Section: Discussionmentioning
confidence: 98%
“…However, the PS-exposed RBC levels in patients with thalassemia were higher than in normal controls. 10 Previous studies showed significantly elevated levels of PS-exposed RBCs in β-thalassemia/Hb E patients who underwent splenectomy and were associated with pulmonary hypertension. 11 This study demonstrated a correlation between PS-exposed RBCs levels and EMH in patients with thalassemia.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, one of our patients with IVCT was found to have hemoglobin H disease, along with other risk factors, including pregnancy and an IVC filter. Hemoglobin H disease, also known as α-thalassemia intermedia, has been identified as a hypercoagulable state with the demonstration of elevated thrombotic biomarkers [ 64 , 65 ]. Abnormalities in pathologic red blood cells, activated platelets, endothelial damage, and splenectomy are established mechanisms of thalassemia that could contribute to VTE [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…28,[94][95][96][97] Patients with a prior history of thrombosis should be managed as per RCOG GTG 37a recommendations for patients with additional risk factors. 98 The pro-thrombotic state in patients with alpha NTDT is less clearly defined, 99,100 and patients should be managed on an individualised risk assessment basis. 98 VTE risk assessment should take place at the initial antenatal visit at 7-12 weeks of gestation (Booking Visit), 28 weeks of gestation and during any admissions, including delivery and postpartum, using a recognised risk assessment tool to guide decisions.…”
Section: Thromboprophylaxismentioning
confidence: 99%